PENGEMBANGAN MEDIA GAMES BOOK UNTUK MINAT BACA SISWA KELAS II SDN 141 PEKANBARU - Anggi Wulandari; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the validity of games book learning media in class II Indonesian language subjects at SDN 141 Pekanbaru. This research uses the ADDIE development model with three stages, namely, (1) analysis stage, namely curriculum analysis, needs analysis, media analysis, (2) design stage, namely designing the creation of learning media according to needs, (3 ) the development stage is the validity testing stage. However, in this research the author only took and carried out limited research from the analysis stage to the development stage due to limited costs and time that the author had. Data sources obtained from primary data are teachers and validators. Meanwhile, secondary data is obtained from articles, journals, books, libraries or reports and official sites on the internet. Data collected through interview techniques, questionnaire validation and documentation. The results of this research show that the research on the game book material aspect obtained a score percentage of 87,45% with very valid criteria and the games book media aspect obtained a score percentage of 92% with very valid criteria. Overall, the validity of the games book media obtained an average percentage score of 89,7%, so that the game book media has very valid criteria without revision.